Azole antimycotics differentially affect rifampicin-induced pregnane X receptor-mediated CYP3A4 gene expression - Svecova, Lucie; Vrzal, Radim; Burysek, Ladislav; Anzenbacherova, Eva; Cerveny, Lukas; Grim, Jiri; Trejtnar, Frantisek; Kunes, Jiri; Pour, Milan; Staud, Frantisek; Anzenbacher, Pavel; Dvorak, Zdenek; et al. (Drug metabolism and disposition: the biological fate of chemicals, 2008)
Azole antifungal drug ketoconazole has recently been demonstrated as an inhibitor of a ligand-induced pregnane X receptor (PXR)-mediated transcriptional regulation of the CYP3A4 gene through disruption of PXR interaction with steroid receptor coactivator (SRC)-1. In contrast, other clotrimazole-derived antifungal agents are known as potent inducers of CYP3A4 through PXR. In the present study, we examined effects of azole antimycotics clotrimazole, ketoconazole, econazole, oxiconazole, miconazole, fluconazole, and itraconazole on PXR-mediated expression of CYP3A4. We investigated individual effects of the tested azoles as well as their action on rifampicin-induced PXR-mediated transactivation and expression of CYP3A4 in LS174T cell line and primary human hepatocytes, their interactions with PXR ligand-binding domain, and azole-mediated recruitment of SRC-1 to PXR. In addition, applying the pharmacodynamic approach and dose-response analysis, we aimed to describe the nature of potential interactions of tested azole antimycotics coadministered with a prototypical PXR ligand rifampicin in transactivation of CYP3A4 gene. We describe additive and antagonistic interactions of partial and full agonists of PXR nuclear receptor in the therapeutic group of azole antimycotics in rifampicin-mediated transactivation of CYP3A4. We show that oxiconazole is a highly efficacious activator of CYP3A4 transactivation, which could be antagonized by rifampicin in a competitive manner. In addition, we show that activation of the CYP3A4 promoter is a complex process, which is not exclusively determined by azole-PXR interactions, and we suggest that the ability of some azoles to affect recruitment of SRC-1 to PXR modulates their net effects in transactivation of CYP3A4 both in the absence or presence of rifampicin.
Keywords: Azoles; azoly; steroidní receptory; Promoter Regions, Genetic; Cells, Cultured; buněčné linie; Humans; systém (enzymů) cytochromů P-450; lidé středního věku; Cell Line; nádorové buněčné linie; Middle Aged; zvířata; Genes, Reporter; messenger RNA; Antifungal Agents; mužské pohlaví; Cytochrome P-450 CYP3A; promotorové oblasti (genetika); antifungální látky; Hepatocytes; kultivované buňky; Pregnane X Receptor; Chlorocebus aethiops; hepatocyty; ženské pohlaví; transfekce; rifampin; Female; Gene Expression; Transfection; reportérové geny; Animals; pregnanový X receptor; RNA, Messenger; lidé; Receptors, Steroid; Rifampin; Aged; senioři; Cell Line, Tumor; Cytochrome P-450 Enzyme System; exprese genu; Male; Cercopithecus aethiops; cytochrom P-450 CYP3A